Religiosity in Context: towards a Deeper Understanding of the Phenomenon - Poplavsky, Roman (Studia religiologica, 2013)
The article deals with the contemporary study of religiosity. The author addresses two core questions of the sociology of religion: what methods are appropriate for the study of religiosity, and what factors affect religiosity? Regarding the first question, contemporary multidimensional studies are described. The author emphasises the limitations of the quantitative method of scales and analyses the criteria of religiosity used in those studies. Considering the factors that affect religiosity and based on Robert Bellah’s theory of religious evolution and Peter Berger’s biographical approach, the author suggests that the historical, cultural, sociopolitical and biographical context should be taken into account in order to better understand the phenomenon of religiosity. Considering the limitations of quantitative methods, it is suggested that they be combined with qualitative methods. Special attention is paid to the studies carried out in the former Soviet Union.